THE ROLE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF COMMERCIAL BANKS (Academicia Globe: Inderscience Research, 2022)
This article describes in detail the improvement of the activities of business entities as modern banking services through the digital banking regulatory system "Digital Bank", its role and importance in the organization of banking services. It is revealed that the digital banking regulator system "Digital Bank" is one of the foundations of the new stage of service and its convenience. It also offers scientific and practical recommendations on further development and improvement of remote banking services provided by commercial banks through the digital banking regulatory system "Digital Bank" and areas for improvement.